Apolipoprotein E-Mimetic Peptide COG1410 Enhances Retinal Ganglion Cell Survival by Attenuating Inflammation and Apoptosis Following TONI - Kuai, Li; Peng, Jianhua; Jiang, Yong; Zheng, Zheng; Zhou, Xiyuan (Frontiers in Neuroscience, 2019)
Vision loss after traumatic optic nerve injury (TONI) is considered irreversible because of the retrograde loss of retinal ganglion cells (RGCs), which undergo inflammation and apoptosis. Previous studies have shown that COG1410, a mimic peptide derived from the apolipoprotein E (apoE) receptor binding region, shows neuroprotective activity in acute brain injury. However, the detailed role and mechanisms of COG1410 in RGC survival and vision restoration after TONI are poorly understood. The current study aimed to investigate the effects of COG1410 on inflammation and apoptosis in a mouse model of TONI. The results showed that TONI-induced visual impairment was accompanied by optic nerve inflammation, apoptosis, edema, and RGC apoptosis. COG1410 significantly prevented the decrease in visual from ever occurring, attenuated inflammation and apoptosis, and reduced optic nerve edema and RGC apoptosis compared with vehicle treatment. These data identify protective roles of COG1410 in the inflammatory and apoptotic processes of TONI, as well as strategies for its treatment.